An evaluation of available treatment technologies to process used oil and depot sludge - Keh, Lily M. (Animo Repository, 2004)
This practicum project aims to present realistic options and recommend a total solution for the prevention, reduction, treatment and disposal of waste generated at oil terminals, e.g. sludge, tank bottoms, and used oil. The present situation of hazardous waste treatment in the Philippines is frustrating because of several factors. These factors include poor government support that result to very few investors in the hazardous waste treatment business, government bureaucracy, and limited capacities of hazardous waste treaters. For an oil product business particularly in Pilipinas Shell Petroluem Corporation (PSPC)- Distribution department, the main functions include receipt, storage, handling and distribution of oil products. After a relative time period, oil stored in vertical tanks and pipelines creates sludge in a form of oily sludge and heavy tank bottom sludge. Over years of operation, hazardous wastes have accumulated and are becoming a serious environmental concern. As a solution to the problem, the proposed project and initiatives under “Closing the Loop” became the answer. The objective of the “Closing the Loop Project” is to recommend the best technology that can treat and dispose depot sludge and used oil. This is a paradigm shift with the hazardous waste transporters and treaters addressing the problem at the source up to its final disposal stage. A change of mindset had to be achieved to develop a new paradigm in handling oily sludge. Representatives from different departments affected by this environmental concern were invited to be part of the team. With so many available technologies present, one treater with the necessary muscle to help in the new paradigm shift has been accredited. The technology involves processing of used oil with sludge to produce an alternative fuel for cement kiln. A treatment process is being used to recover energy, process alternative fuel and raw material for cement kiln. This is called pyrolysis. My role in Pilipinas Shell embodies the Health, Safety, Security and Environment (HSSE) management of the business. Being part of the “Closing the Loop” project, I am in-charge of evaluating available options for treatment and disposal of hazardous waste generated by different oil depots of PSPC. As part of the team, I was tasked to do the following: • Discuss and present available treatment and disposal options of hazardous wastes being generated in the depot • Conduct an initial assessment for disposal of hazardous wastes This is in line with the company’s commitment to safeguard the health and safety of the people as well as environment. The loop in Distribution for hazardous waste treatment and disposal can be closed by utilizing processed depot sludge and used oil as alternative fuel in cement kilns. This practicum report describes the different technologies available and presents the best available solution to the existing hazardous waste treatment and disposal problem of oil terminals.